Rare and Insidious Toxicities from New Combination Therapies in Metastatic Renal Cell Cancer: Lessons Learned from Real-Practice - Arianna Dri; Silvio Ken Garattini; Marika Cinausero; Marianna Macerelli; Martina Fanelli; Fabio Puglisi; Gianpiero Fasola; Paola Ermacora (Current Oncology, 2022)
The advent of immune checkpoint inhibitors in combination with multitarget tyrosine kinase inhibitors has become a standard first-line treatment for metastatic renal cell cancer. Along with survival improvement, new toxicities have emerged. Such adverse events are still complex to be managed and some of them are rare and could be insidious or even fatal. Medical oncologists dispose of guidelines about the management of toxicities from immune checkpoint inhibitors but not for combinations. Therefore, it is still difficult to properly attribute and manage additive or overlapping adverse events. We report two clinical cases regarding rare treatment-related endocrine toxicities—hypophysitis and thyroiditis—with particular focus on their management. To this purpose, immune checkpoint-related toxicities guidelines represent the starting point. However, their implementation with additional measures is needed, considering the increasing complexity of current clinical scenarios. The goal is to correctly recognize adverse events and address side effects, so as not to discontinue effective treatments. We, therefore, aim at discussing the points of proper management of toxicities and individuating potential areas of improvement.